ANALISIS PENGARUH EARNING PER SHARE, DEBT TO EQUITY RATIO, PRICE EARNING RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN KABEL PADA BURSA EFEK INDONESIA - Apriyansyah, Didik; Fitriani, Dyah (Universitas Ahmad Dahlan, 2014)
This research aims to find out whether there is an effect of Earning Per Share (EPS), Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Return On Equity (ROE) against the cable company’s share price listed on the Indonesia Stock Exchange period 2005-2009. While the types of data used are secondary data with a sample of 5 of 6 populations of the company. Sampling was purposive sampling. Data analysis tools used in this study is the multiple linear regression using a significance level of 0.05, test analysis T-test and analysis of the coefficient of multiple determination (R2). From the test results obtained by T-test significant value variable earnings per share have significant effect on stock prices, while the variable debt to equity ratio, price earnings ratio and return on equity does not have a significant influence to share price cable companies listed in Indonesia Stock Exchange (BEI in the period 2005-2009. The results of coefficient of determination (R2) obtained the value R Square of 0.423.